Community Psychology in higher education in Europe: Results of a survey and discussion of the basic competency approach. (6th March 2020) - Roehrle, Bernd; Akhurst, Jacqui; Carr, Nicholas; Herrera Sánchez, Isabel M.; Arcidiacono, Caterina; Lawthom, Rebecca; Stark, Wolfgang
Abstract: This report from the Standing Committee on Community Psychology of the European Federation of Psychological Association provides an overview of higher education in Community Psychology (CP) in 14 European countries. Our findings show that 10 countries have some kind of CP teaching in their educational system. Twenty European universities offer a CP‐oriented Master degree, two universities at the Bachelor level and 16 universities also have CP‐oriented Ph.D. programmes. The profiles of the universities focus on two areas: Community psychology in a pure form and a combination of social psychology and community psychology. The other universities vary between clinical, organisational psychology, and a pedagogical focus. Within a certain European emphasis, these universities are analysing and changing the social conditions of community life and mental health. The responding universities failed to report adequately on comprehensive core competences and key elements in CP. To compensate for this deficit, the Standing Committee on Community Psychology proposes to develop a primer of basic CP competences for inclusion in programmes like EuroPsy.